Hubungan Tingkat Pengetahuan Ibu tentang Vitamin A dengan Pemberian Kapsul Vitamin A pada Balita - Mahlida Mahlida; Fitriani Ningsih; Riska Ovany (Jurnal Surya Medika (JSM), 2022)
Vitamin A is one of the essential nutrients that are fat-soluble and stored in the liver, the body cannot make it, so it must be met from the outside (essential). Another most severe consequence of vitamin A deficiency (VAC) is night blindness, another form of xerophthalmias such as corneal damage and blindness. Vitamin A can increase the body's resistance to infectious diseases such as measles, diarrhea, and ARI and has a vital role in health eye. This study determined the relationship between a mother's level of knowledge about vitamin A and giving vitamin A to toddlers based on the data through the literature review method. They are using the literature review method. Journal searches use an academic database, namely Google Scholar, published in 2017-2020 using Indonesian and English. Cross-sectional study design. They obtained six research results according to the inclusion criteria. The research sample averaged 38-100 respondents. The results of the research analysis showed in six research journals that there was a relationship between the mother's level of knowledge about vitamin A and giving vitamin A capsules to toddlers with A mother's awareness of the importance of vitamin A in toddlers can be seen in the knowledge they have, one of the causes of the problem of vitamin A deficiency is the behavior or attitude of mothers who do not give vitamin A to their children. This is based on a lack of knowledge about the importance of vitamin A. P-value = 0.005. A mother's awareness of the importance of vitamin A in toddlers can be seen from the inside. One of the causes of vitamin A deficiency is the behavior or attitude of mothers who do not give vitamin A to their children. This is based on a lack of knowledge about the importance of vitamin A.